Povezave med izbranimi dejavniki tveganja in pojavnostjo bolečine v križu pri zdravstvenem osebju - Demšar, Andreja (Obzornik zdravstvene nege, 2016)
Introduction: Low back pain is a common health complaint among health care workers. The aim of the study was to identify the prevalence of low back pain among health care personnel in relation to selected risk factors. Methods: The study is based on a non-experimental quantitative method of empirical research. A close-ended questionnaire on low back pain was used and completed by 89 health care workers at the General Hospital Jesenice and retirement home in the Gorenjska region. A Chi-square and one-way ANOVA were computed to establish statistically significant differences between the groups. Results: In 40.4 % of respondents low back pain occurs several times a month, mostly among nursing assistants (p = 0.001) and those working in nursing units (p = 0.006). On average, the pain lasts less than a week (43.8 %). The factor that is most commonly associated with low back pain is lifting and carrying of loads (x = 4.5). Statistically significant differences were revealed between occupational groups in terms of knowledge on low back pain and correct load lifting techniques (p < 0.010). Discussion and conclusion: Low back pain is most frequently associated with direct physical contact with patients. Further research with larger representative sample size will be required. Education and counselling to prevent low back pain in nurses is recommended along with the use of devices for safe patient handling
Keywords: bolečina; bolničarji; dejavniki tveganja; delovno mesto; doctors; hrbtenica; medicinske sestre; nurses; nursing assistants; pain; risk factors; spine; workplace; zdravniki